Study of Gross Anatomy of Human Placenta in Pregnancy Induced Hypertension (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Pregnancy induced hypertension (PIH), also referred to as Gestational hypertension is a condition of high blood pressure during pregnancy. Progression the disease causes preeclampsia and eclampsia, which are the commonest causes of maternal and fetal morbidity and mortality.Objective: The objectives of the study were to observe and measure the macroscopic changes in the placenta in pregnancy induced hypertension and to compare the placental findings of the control group. .Method: This descriptive observational study was carried out in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU). Forty placentas were collected from Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) and Bangabandhu Sheikh Mujib Medical University. Out of forty placentas, twenty were from non-hypertensive mother considered as controls and twenty from PIH mothers. Mother who had Rh-negative blood group, positive for VDRL and HbsAg and mother delivered multiple babies or babies with any visible congenital malformation were excluded. All women included in the study gave birth to a live born baby after 35 weeks of gestation by caesarian section. The macroscopic features of placentas were recorded and after that specimen was fixed in 10% formol saline. After two week of fixation, a point counting method was used on placental slices for estimation of the volume of parenchyma and non-parenchyma.Results: The general features of the control and PIH mother were statistically matched. As compared with the control group, PIH group showed no statistically significant difference in values of placental weight, volume and diameter.Mean placental weight (gm), mean volume (ml) and the mean diameter (cm) of the placental, mean absolute volume of parenchyma, mean proportional and mean absolute volume of non-parenchyma were lower in PIH group than the control group. The mean number of cotyledon of the placenta and mean proportional volume of parenchyma were higher in PIH group than control group and. These differences did not reach statistically significant level.Conclusion: Several authors has concluded that the changes in the placenta in diabetic and toxaemic mother are the reflection of some compensatory mechanism, but the present study fails to identify any statistically significant changes in PIH group in favour of such statement.Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014